Associations of maternal age at the start of pregnancy with placental function throughout pregnancy: The Generation R Study. (August 2020) - Erkamp, Jan S.; Jaddoe, Vincent W.V.; Mulders, Annemarie G.M.G.J.; Duijts, Liesbeth; Reiss, Irwin K.M.; Steegers, Eric A.P.; Gaillard, Romy
Abstract: Objective: To examine the associations of maternal age at the start of pregnancy across the full range with second and third trimester uterine and umbilical artery flow indices, and placental weight. Study design: In a population-based prospective cohort study among 8271 pregnant women, we measured second and third trimester uterine artery resistance and umbilical artery pulsatility indices and the presence of third trimester uterine artery notching using Doppler ultrasound. Results: Compared to women aged 25−29.9 years, higher maternal age was associated with a higher third trimester uterine artery resistance index (difference for women 30−34.9 years was 0.10 SD (95% Confidence Interval (CI) 0.02 to 0.17), and for women aged ≥40 years 0.33 SD (95% CI 0.08 to 0.57), overall linear trend 0.02 SD (95% CI 0.01 to 0.03) per year). Compared to women aged 25−29.9 years, women younger than 20 years had an increased risk of third trimester uterine artery notching (Odds Ratio (OR) 1.97 (95% CI 1.30–3.00)). A linear trend was present with a decrease in risk of third trimester uterine artery notching per year increase in maternal age (OR 0.96 (95% CI 0.94 to 0.98)). Maternal age was not consistently associated with umbilical artery pulsatility indices or placental weight. Conclusions: Young maternal age is associated with higher risk of third trimester uterine artery notching, whereas advanced maternal age is associated with a higher third trimester uterine artery resistance index, which may predispose to an increased risk of pregnancy complications.